Multi-Camera Panoramic Imaging System Based on Adaptive Brightness Uniformization For The Truck. (December 2020) - Cheng, Bang; Sun, Tongyi; Cheng, Jianghua; Liu, Tong
Abstract: With the development of science technology and logistics industry, the transportation of large trucks is also indispensable. It is also accompanied by many traffic accidents. The paper mainly focuses on the problem of blind spots in the parking of large trucks. A panoramic imaging system with six cameras is implemented to improve its safety performance. It mainly includes the realization of modules included simultaneous acquisition of images by multiple cameras, image calibration and correction, top view image generation, image stitching and image fusion. In view of the brightness difference of images acquired by different cameras, we proposed an adaptive brightness uniformization method based on γ-transformation. Meanwhile, we compared the proposed method with various image enhancement methods included histogram equalization, Laplace operator and logarithm transformation. The experimental results in the system demonstrate the superiority of our proposed method compared to others.